The Effects of Dynamic Work Environments on Entrepreneurs’ Humble Leader Behaviors: Based on Uncertainty Reduction Theory - Deng, Xiao; Gao, Bo; Li, Guozheng (Frontiers in Psychology, 2019)
Although it is widely acknowledged that the environments faced by entrepreneurs now are more dynamic than ever, little is known about the effect of dynamic work environments on entrepreneurs’ leader behaviors. Based on the uncertainty reduction theory and the data from 197 entrepreneurs and their subordinates, this research found a positive relationship between dynamic work environments and entrepreneurs’ humble leader behaviors. Moreover, this positive relationship can be mediated by entrepreneurs’ feedback-seeking behavior. And the relationship between dynamic work environments and entrepreneurs’ humble leader behaviors (via feedback-seeking) can be moderated by entrepreneurs’ intolerance of uncertainty. The contributions and implications of this study are discussed.